1994
DOI: 10.1007/bf01321068
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and sequence analysis of the 3′-terminal region of iris severe mosaic virus RNA

Abstract: Sequence analysis of iris severe mosaic potyvirus genomic RNA revealed an unusual E/G cleavage site between the deduced large nuclear-inclusion protein and coat protein sequences. The latter showed an N-terminus of only 15 amino acids. The 3' non-translated region of the viral RNA was 340 nucleotides long.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…To our knowledge, it is the first report of ISMV occurrence in Iran. We found that ISMV-Ir was not able to infect the number of mechanically inoculated test plant species, which was similar to the results of previous research carried out by Barnett et al (1971), Brunt et al (1980Brunt et al ( , 1988, Derks and Hollinger (1986), Van der Vlugt et al (1994). Only a couple of tested plant species (C. vernus and I. domestica) are diagnostically susceptible to ISMV.…”
Section: Rt-pcr Sequencing and Phylogenetic Analysissupporting
confidence: 91%
“…To our knowledge, it is the first report of ISMV occurrence in Iran. We found that ISMV-Ir was not able to infect the number of mechanically inoculated test plant species, which was similar to the results of previous research carried out by Barnett et al (1971), Brunt et al (1980Brunt et al ( , 1988, Derks and Hollinger (1986), Van der Vlugt et al (1994). Only a couple of tested plant species (C. vernus and I. domestica) are diagnostically susceptible to ISMV.…”
Section: Rt-pcr Sequencing and Phylogenetic Analysissupporting
confidence: 91%
“…Iris severe mosaic virus (ISMV) is a member of the genus Potyvirus in the family Potyviridae and possesses flexuous filamentous particles and a single-stranded positive-sense RNA genome (1). ISMV has been detected in plants in the family Iridaceae (2). ISMV causes chlorotic stripes and mosaic symptoms on the leaves and color breaking on the petals.…”
Section: Announcementmentioning
confidence: 99%